Role of Exercise Training on Autonomic Changes and Inflammatory Profile Induced by Myocardial Infarction - Rodrigues, Bruno; Lira, Fabio S. [UNESP]; Consolim-Colombo, Fernanda M.; Rocha, Juraci A.; Caperuto, Erico C.; De Angelis, Katia; Irigoyen, Maria-Claudia (Hindawi Publishing Corporation, 2014)
The cardiovascular autonomic imbalance in patients after myocardial infarction (MI) provides a significant increase in mortality rate, and seems to precede metabolic, hormonal, and immunological changes. Moreover, the reduction in the parasympathetic function has been associated with inflammatory response in different pathological conditions. Over the years, most of the studies have indicated the exercise training (ET) as an important nonpharmacological tool in the management of autonomic dysfunction and reduction in inflammatory profile after a myocardial infarction. In this work, we reviewed the effects of ET on autonomic imbalance after MI, and its consequences, particularly, in the post-MI inflammatory profile. Clinical and experimental evidence regarding relationship between alterations in autonomic regulation and local or systemic inflammation response after MI were also discussed.